Cone-beam CT reconstruction with gravity-induced motion. (16th October 2018) - Shieh, Chun-Chien; Barber, Jeffrey; Counter, William; Sykes, Jonathan; Bennett, Peter; Heng, Soo-Min; White, Paul; Corde, Stéphanie; Jackson, Michael; Ahern, Verity; Feain, Ilana; O'Brien, Ricky; et al.
Abstract: Fixed-gantry cone-beam computed tomography (CBCT), where the imaging hardware is fixed while the subject is continuously rotated 360° in the horizontal position, has implications for building compact and affordable fixed-gantry linear accelerators (linacs). Fixed-gantry imaging with a rotating subject presents a challenging image reconstruction problem where the gravity-induced motion is coupled to the subject's rotation angle. This study is the first to investigate the feasibility of fixed-gantry CBCT using imaging data of three live rabbits in an ethics-approved study. A novel data-driven motion correction method that combines partial-view reconstruction and motion compensation was developed to overcome this challenge. Fixed-gantry CBCT scans of three live rabbits were acquired on a standard radiotherapy system with the imaging beam fixed and the rabbits continuously rotated using an in-house programmable rotation cradle. The reconstructed images of the thoracic region were validated against conventional CBCT scans acquired at different cradle rotation angles. Results showed that gravity-induced motion caused severe motion blur in all of the cases if unaccounted for. The proposed motion correction method yielded clinically usable image quality with  <1 mm gravity-induced motion blur for rabbits that were securely immobilized on the rotation cradle. Shapes of the anatomic structures were correctly reconstructed with  <0.5 mm accuracy. Translational motion accounted for the majority of gravity-induced motion. The motion-corrected reconstruction represented the time-averaged location of the thoracic region over a 360° rotation. The feasibility of fixed-gantry CBCT has been demonstrated. Future work involves the validation of imaging accuracy for human subjects, which will be useful for emerging compact fixed-gantry radiotherapy systems.